A study of the effects of organic matter on illitization in the Woodford Shale, Oklahoma and Kansas - Janssen, Kale W. (Kansas State University, 2017)
The Woodford Shale has received significant research interest as the number of productive wells has increased. The Woodford is productive over a wide range of thermal maturity (based upon vitrinite reflectance), yet most clay mineral studies report primarily illite (Caldwell, 2011 & Whittington, 2009). A previous report contrasts this behavior to other late Paleozoic shales in Oklahoma (Kowal, 2016). The major difference between these units is the amount of organic matter, which is much higher in most Woodford samples. In this study, Woodford shale samples were analyzed for several different characteristics, and combined with organic fraction data from previous work on the same samples (Lambert, 1993). Clay mineralogy was determined using an X-ray diffractometer (XRD) with the goal of finding the amount, and the degree of crystallinity of illite in a suite of samples. X-ray fluorescence (XRF) analysis was conducted to determine the variability of elemental concentrations within the samples. The bulk powder XRD data were combined with the major element concentrations to calculate mineral percentages. These data were compared to thermal maturity based upon vitrinite reflectance and Tmax values to determine the role of burial diagenesis on the clay mineralogy within Woodford Shale. The predominant clay mineral found within the samples was illite, with no recognizable mixed-layer smectite present, suggesting illitization is occurring early in the diagenetic process. A positive correlation between K/Rb ratios and TOC was found, supporting the control of organic matter on potassium in shales. No correlation between amount illite and thermal maturity was found, providing more evidence for the theory that high amounts of organics are driving illitization rather than thermal maturity.
Keywords: Woodford Shale illitization